Monday

July 28, 2014

July 28, 2014

Posted by **Mike** on Thursday, November 11, 2010 at 5:55am.

cott^2/csct=csct-sint

- Trig -
**Reiny**, Thursday, November 11, 2010 at 7:42amAre you showing that they are identities ?

if so,

LS = (sin^2t/cos^2t)(cost)

= sin^2t/cost

RS = 1/cost - cost

= (1 - cos^2t)/cost

= sin^2t/cost

= LS

The second one works the same way, try it.

**Related Questions**

Trig - (cos^2t+4cos^2+4)/(cost+2)=(2sect+1)/sect

Trig - Prove cos^2t+4cost+4/cost+2=2sect+1/sect

Trig - Prove cos^2t+4cost+4/cost+2=2sect+1/sect

Trig - Prove cos^2t+4cost+4/cost+2=2sect+1/sect

Trig - Prove (cos^2t+4cos^2+4)/(cost+2)=2sect+1)/sect

pre calculus - simplify *cost tant * cost csct

math 191- calc - sect + tan t= (sqr 3)

Calculus - Could someone please check my work on the following problems? I want ...

trig - Q1: Prove cos^2t+4cost+4/cost+2=2sect+1/sect Q2: A ship leaves port with ...

sociology perspective - A person is hiking in the Canyonlands of Utah, and she ...